2022
DOI: 10.1590/1806-9282.20210811
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of C-reactive protein and C-reactive protein-to-albumin ratio in predicting mortality among geriatric coronavirus disease 2019 patients

Abstract: OBJECTIVE:The aim of this study was to evaluate and compare C-reactive protein and C-reactive protein-to-albumin ratio performances in predicting mortality of geriatric patients who visited the emergency department. METHODS:The data of patients with COVID-19 and aged 65 years and above, who visited emergency department during the study period, were retrospectively analyzed. The data were obtained from an electronic-based hospital information system. The area under the receiver operating characteristic curve an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…A previous study explored the clinical relevance of the C-reactive protein-to-albumin (CRP/CAR) ratio for in-hospital mortality in patients with coronavirus disease 2019 (COVID-19) 2 . In this study, the findings revealed that both CRP and CRP/CAR ratio were effective in predicting mortality in elderly COVID-19 patients 1 . However, from our point of view, there are several issues that need to be addressed further in this investigation.…”
mentioning
confidence: 58%
See 1 more Smart Citation
“…A previous study explored the clinical relevance of the C-reactive protein-to-albumin (CRP/CAR) ratio for in-hospital mortality in patients with coronavirus disease 2019 (COVID-19) 2 . In this study, the findings revealed that both CRP and CRP/CAR ratio were effective in predicting mortality in elderly COVID-19 patients 1 . However, from our point of view, there are several issues that need to be addressed further in this investigation.…”
mentioning
confidence: 58%
“…We read with interest the article entitled “Comparison of C-reactive protein and C-reactive protein-to-albumin ratio in predicting mortality among geriatric coronavirus disease 2019 patients.” 1 . A previous study explored the clinical relevance of the C-reactive protein-to-albumin (CRP/CAR) ratio for in-hospital mortality in patients with coronavirus disease 2019 (COVID-19) 2 .…”
mentioning
confidence: 99%
“…Therefore, serum albumin level would cause a reduction in inflammatory diseases. [18] In a multicenter study conducted with the data of 2461 AP patients, it was reported that mortality would increase more than 16 times if hypoalbuminemia was present in AP patients who admitted to the hospital. [19] The third variable of the HALP score, the lymphocyte, is a portion of the white blood cells.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of nutritional problems, sepsis, severe trauma, malignancy, and severe inflammation, low albumin levels can be observed due to increased vascular permeability [15]. It has been shown that hypoalbuminemia is associated with mortality in critically ill patients [16]. In a study conducted in Italy, the data of 319 COVID-19 patients were examined, and when the patients were divided into survivor and nonsurvivor groups, the nonsurvivor group was determined to have lower albumin levels at the time of admission [17].…”
Section: Discussionmentioning
confidence: 99%